Remote music teaching during 2020: teaching and digital literacy of two teachers (DAPesquisa, 2021)
Faced with the reality of a pandemic, in this work we intend to understand the impacts of distance music education, during the year 2020, through the narrative of two teachers who attend public schools. To experience two teachers with narrative, telling stories of their own life and their teaching experiences during the isolation period, they insert or work within the so-called biographical movement of education. The low stimulus for teaching professionals, combined with the lack of social programs aimed at greater access to the internet or digital technologies by two students and their families, present in the teachers reports, revealed challenges of the moment experienced in basic education in 2020.
Keywords: Music teachers; Open learning; Oral History; COVID-19 Pandemic, 2020